A constituição identitária do idoso na literatura infantojuvenil - Simonetti, Marivane (2016)
This work is the result of a research with the topic Elderly in Children's Literature and the analysis of three contemporary Brazilian children's literary works: O guarda chuva do vovô (2008), Vovô foi viajar (1997) and O Olho de vidro do meu avô (2009). These works were analyzed to identify the image of the elderly showed by them. First, the history of Children's Literature and its definitions is presented, then data about the elderly theme and its importance within this literature is raised, in the sequence, the Programa Nacional Biblioteca na Escola (PNBE) is studied –this is a program that distributed the books analyzed in public schools across the country- and eventually the works analyzed are described. The research consisted of a bibliographic study, through the collection of data in books, magazines, articles and publications in electronic media. The Estatuto do Idoso, and the authors Nelly Novaes Coelho, Ligia Cademartori, Alex Confort and Monica Todaro were the main references used to develop this research. For the analysis were used aspects such as: characters, plot and theme. The study results in a contribution regarding how the identity of the Elderly is constituted in the works of Children's Literature. In this way it was possible to infer about the way the elderly have been treated in Children's Literature and if the way they are portrayed in the books is the ideal.